EcoLinguistic Insights in Nias Village Name: Unravelling the Dynamic Bond Between Language and Environment - Hadi, Wisman; Mulyono, Mulyono (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2023)
Ecological structures hold profound significance in the identification and naming of localities within Nias villages. This significance underscores the dynamic bond between language and the environment, forming a foundational aspect of the local ethnicity. This study endeavors to delve into the ecological significance that underpins the naming of Nias villages, elucidating the intricate connection between language and the environment upon which village names are founded. In pursuit of this objective, the research engages with a purposive sample of 20 informants, representing 151 localities within Nias. Through in-depth interviews, valuable insights are gathered and transcribed to constitute the research data. Employing a descriptive qualitative design, the study leverages a semantic representation protocol to categorize data according to the ecological units embedded in the village names. The investigation's findings reveal that the Nias villages predominantly employ the Nias language lexicon. Notably, 55 villages incorporate the lexicon